Digital literacy requires school resilience - Nopita Sitompul; Siti Irene Astuti Dwiningrum; Safitri Yosita Ratri; Rukiyati Rukiyati; Annisa Setyaningrum; Ebni Sholikhah; Anindita Ayu Nisa Utami (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2023)
Digital literacy requires school resilience. The purpose of this study is to describe the profile of school resilience and strategies for strengthening school resilience in order to strengthen digital literacy. The method used in this study is a descriptive method that combines quantitative and qualitative (mix method). The research was conducted at SMN N 1 Mungkid involving 40 teachers and 100 students with a multistage random sampling model. The sampling technique in this study was determined using the Lameshow formula, with a total sample of 140 people. Data collection techniques were also carried out using a questionnaire technique through online media (google form) and documentation. The analytical technique used is descriptive with the Excel program using a categorization method based on percentage calculations. The results showed that the overall resilience of Mungkid Junior High School in facing the digital literacy era according to teachers and students was at the lower score, which is in the category of positive resilience building scale (teachers: 31%; Students: 40%). The strategy for strengthening school resilience in the digital literacy era are (1) adapting to situations and conditions, (2) school intervention in overcoming environmental risks and transitions, (3) identifying factors that can help schools overcome crises, (4) skills mapping to identify training needs, (5) identifying the strengths and weaknesses of the education system, and (6) documenting the learning gained by taking into account the availability of school human resources (HR), continuous professional development, communication, network support, adaptation and knowledge-based development.